The impact of the COVID-19 epidemic on higher education: Opportunities and implications for policy and practice - Turgut Karakose (ÜNİVERSİTEPARK Limited, 2021)
Background/purpose - Besides many psychological, sociocultural, political, and economic problems, the COVID-19 pandemic has also led to radical changes in education systems worldwide, and the current pandemic has probably revealed the biggest education crisis in human history. The COVID-19 pandemic also offered significant opportunities to redesign higher education and to develop and implement effective teaching-learning strategies. The purpose of this article is to discuss the effects of the COVID-19 pandemic on higher education from a global perspective. Materials/methods - This paper is a review article; presenting a brief literature review on the COVID-19 pandemic and higher education. Practical implications - This article is aimed at inspiring both researchers and practitioners with regards to future research perspectives on COVID-19 and higher education. In this context, the responses of higher education institutions to the global education crisis caused by the current pandemic were examined, and some solution proposals were developed for policymakers and higher education professionals. Conclusion - The COVID-19 pandemic resulted in the worldwide education community acknowledging the fact that urgent adoption of an online emergency remote teaching approach was both necessary and inevitable.